Letter : Scottish Ambulance Unit in Spain - Stott, William
041-0130-001 Telegraphic Address:" FORESHADOW. NORWEST, LONDON" (as two words). RAILWAY CLERKS' ASSOCIATION OF GREAT BRITAIN AND IRELAND Representing the Clerical, Administrative, Professional, Technical, and Supervisory' Employees in all Departments of the Railway Service. General Secretary: WILLIAM STOTT. Telephone: Terminus 6267 (3 lines) In your reply P. please quote this reference. Registered Office — 25, Euston Road, LONDON, N.W.1 30th October, 1936. Sir Walter Citrine, K.B.E., General Secretary, T.U.C. General Council, Transport House (South Block), Smith Square, Westminster, S.W.1. Dear Sir Walter, SCOTTISH AMBULANCE UNIT IN SPAIN. I have been asked if I can do anything to induce the British T.U.C. to make a grant to the Scottish Ambulance Unit that is now in Spain. I gather that the Unit is experiencing financial difficulties, and will have to be recalled unless more support is forthcoming. One of the members of the Unit is the son of Mr. C.N. Gallie, the Scottish Secretary of the R.C.A., and a member of the General Council of the Scottish Trades Union Congress, and he has learned from his son that the Scottish Ambulance Unit is alleviating to a very great measure the sufferings of a large number of refugees, as well as wounded people. Reports from neutral sources and from the Press give high praise to this Scottish Unit, and the British Charge d'Affaires at Madrid has complimented them on their magnificent work. I trust, therefore, it may be possible for a grant from the International Solidarity Fund to be made to the Scottish Ambulance Unit. Yours sincerely W. Stott 292/946/41/130